Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/app12020651
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Business Intelligence and Analytics-Based Healthcare Facility Management Key Performance Indicators

Abstract: The use of digital technologies such as Internet of Things (IoT) and smart meters induces a huge data stack in facility management (FM). However, the use of data analysis techniques has remained limited to converting available data into information within activities performed in FM. In this context, business intelligence and analytics (BI&A) techniques can provide a promising opportunity to elaborate facility performance and discover measurable new FM key performance indicators (KPIs) since existing KPIs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 182 publications
1
10
0
Order By: Relevance
“…Furthermore, maintenance programming in hospitals is still purely subjective, where FMs categorize the IOP Publishing doi:10.1088/1755-1315/1176/1/012014 8 importance and priority levels of different interventions and plan them according to the associated cost [26]. Demirdöğen, G. et al [27] in a deep literature review in the business intelligence and analytics (BI&A) context identified more than one hundred and sixty FM key performance indicators (KPIs), and almost one hundred were found to be usable in healthcare FM performance benchmarking. These FM KPIs give clues about BIM information types to perform performance management with BIM and obtain dynamic data requirements of BIM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, maintenance programming in hospitals is still purely subjective, where FMs categorize the IOP Publishing doi:10.1088/1755-1315/1176/1/012014 8 importance and priority levels of different interventions and plan them according to the associated cost [26]. Demirdöğen, G. et al [27] in a deep literature review in the business intelligence and analytics (BI&A) context identified more than one hundred and sixty FM key performance indicators (KPIs), and almost one hundred were found to be usable in healthcare FM performance benchmarking. These FM KPIs give clues about BIM information types to perform performance management with BIM and obtain dynamic data requirements of BIM.…”
Section: Discussionmentioning
confidence: 99%
“…FMs today have large amounts of data that require time and resources. Furthermore, the key to scheduling when a necessary intervention is needed depends on the ability to predict the future condition of the asset and, in most cases, the interconnections between the building's various mechanisms and systems, the diversity of building components, and various changing environmental factors are neglected [27]. Thus, AI can intelligently connect this data, while humans' ability to process this information is often limited.…”
Section: Discussionmentioning
confidence: 99%
“…They require a large amount of detailed data in order to model a scenario that is useful, i.e., statistically valid. This is a suitable approach for formulating and improving sectoral policies, standards, and indicators, such as KPIs [10,28]. The application of these models in single cases, such as a building complex, is less common because the conditions for the operation of such models are available only in restricted socioeconomic, technological, and institutional contexts where massive amounts of data are available, for example, in studies with access to data that were recorded through capture technologies, such as real-time location-based services (RTLS) [2,10,41].…”
Section: Pre-design Evaluation (Pde) Models and Performance Simulationsmentioning
confidence: 99%
“…Evidence-based design (EBD) allows for the improvement of the design decisions for planned or existing environments [3,5,6]. Research that is oriented toward design and facility management (FM) has also focused on mapping, modeling, and simulating the building performance [7], behavior [8,9], and organization [10], the allocation of resources [4,11], the flow of people and activities [9,11], the operational efficiency [12,13], the space and layout [14,15], and the optimal paths [16]. Among the existing modeling, simulation, and evaluation methods, there is a lack of straightforward and logical resources that can be used to assess whether the allocation of activities in a built environment is congruent.…”
Section: Introductionmentioning
confidence: 99%
“…It is primarily used in a wide range of decision-making scenarios and has a specific use in decision-making. In business and management related research, the POMETHEE has been used in bankruptcy prediction (Hu & Chen, 2011), and recently used in measuring key performance indicators (Demirdöğen, et al 2022). By utilising PROMETHEE II, Mousavi & Lin (2020) expanded the use of expert systems to anticipate business credit risk and financial distress.…”
Section: Related Researchmentioning
confidence: 99%